Carbon-based Composites for Environmental Clean-up: Advances in Biochar, g-C3N4, Graphene Oxide and CNTs - Bhattacharjee, Baishali; Mishra, Soumya Ranjan; Gadore, Vishal; Ahmaruzzaman, Md (Journal of the Taiwan Institute of Chemical Engineers, 2025)
•The review highlights potentials of carbonaceous materials for water treatment.•Synthesis, structures, and properties of BC, GO, CNTs, and g-C3N4 are discussed.•Photodegradation of toxic contaminants with phenolic compounds has been summarized.•The review gives an in-depth look for environmental restoration for last 4–5 years.•Scope of further research has been provided to understand the topic better. Photodegradation of harmful pollutants has received a lot of attention in recent years as an eco-friendly and sustainable way to clean up polluted areas. Carbon-based composites, including biochar, graphene oxide (GO), carbon nanotubes (CNT), and graphitic carbon nitride (g-C3N4), have shown potential as efficient photocatalysts for breaking down a wide range of harmful contaminants, including dyes, pharmaceuticals, pesticides, phenolic compounds, and heavy metals. This review paper gives an in-depth look at the most recent breakthroughs in using carbon-based materials for environmental restoration during the previous 4–5 years. The study begins by reviewing the various synthesis strategies used to generate biochar, graphene oxide, CNTs, and g-C3N4-based composites, stressing their benefits and limits. Following that, the properties and characteristics of these carbon-based materials are thoroughly studied, providing light on the unique traits that make them suited for photocatalytic applications. The article digs into a detailed examination of current breakthroughs in the field of carbon-based composites for the photodegradation of harmful contaminants at the heart of this review. The topic includes creative methodologies, novel materials, and promising advances in catalytic processes, emphasizing the potential for improved pollutant degradation and increased environmental sustainability. Special emphasis is placed on studies published between 2020 and 2024, giving readers a full grasp of the most recent research on this expanding subject. It emphasizes the rising importance of carbon-based photocatalysts in solving environmental issues and lays the groundwork for future research approaches. Finally, this review paper is a helpful resource for academics, scientists, and environmental regulators interested in current breakthroughs in carbon-based composites for harmful pollutant photodegradation. It emphasizes the crucial significance of these materials in long-term environmental cleanup and provides a detailed overview of the research. [Display omitted]